2017
DOI: 10.1128/jvi.01372-17
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Transmission of Hepatitis C Virus: Variable Transmission Bottleneck and Evidence of Midgestation In Utero Infection

Abstract: Hepatitis C virus (HCV) can be transmitted from mother to child during pregnancy and childbirth. However, the timing and precise biological mechanisms that are involved in this process are incompletely understood, as are the determinants that influence transmission of particular HCV variants. Here we report results of a longitudinal assessment of HCV quasispecies diversity and composition in 5 cases of vertical HCV transmission, including 3 women coinfected with human immunodeficiency virus type 1 (HIV-1). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
0
13
0
2
Order By: Relevance
“…HCV is transmitted mainly through parenteral routes such as infected blood transfusion, intravenous drug use or blood product, therapeutic injection, intravenous drug use, acupuncture, tattooing, ear piercing and transmission during sexual contact and vertically from infected-mother-to-child [5,11,12].Vertical transmission of HCV from mother-to-child contributes to 10% of cases and lower than other viral pathogens such as HIV and HBV [13]. Drugs like direct-acting antiviral agents (DAA) are effective for curing up to 70% of HCV-infected persons; however, contraindicated during pregnancy [11,13]. Currently, there is no effective vaccine for HCV and no effective means of preventing MTCT of HCV.…”
Section: Introductionmentioning
confidence: 99%
“…HCV is transmitted mainly through parenteral routes such as infected blood transfusion, intravenous drug use or blood product, therapeutic injection, intravenous drug use, acupuncture, tattooing, ear piercing and transmission during sexual contact and vertically from infected-mother-to-child [5,11,12].Vertical transmission of HCV from mother-to-child contributes to 10% of cases and lower than other viral pathogens such as HIV and HBV [13]. Drugs like direct-acting antiviral agents (DAA) are effective for curing up to 70% of HCV-infected persons; however, contraindicated during pregnancy [11,13]. Currently, there is no effective vaccine for HCV and no effective means of preventing MTCT of HCV.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are limited, due to challenges in follow-up; in a large US city, only 5% of infants born to HCVpositive mothers received appropriate testing. (41) The timing of vertical transmission can vary from midgestation (in utero) (42) to the time of delivery. (43) Peripartum transmission is believed to be due to infant exposure to infected blood or body fluids, whereas in utero transmission is influenced by immune-modulating effects of pregnancy, with loss of selective pressure on viral replication and associated increased proliferation of viral quasispecies with optimized replicative fitness.…”
Section: Rate Timing and Contributing Factors To Mother-to-child Trmentioning
confidence: 99%
“…One study evaluated HCV‐exposed neonates and found them to have lower levels of regulatory T cells and rates of clusters of differentiation (CD)4+ and CD8+ T‐cell activation as well as lower plasma levels of proinflammatory markers than controls, suggesting a relative suppression of immune activation in neonates exposed to HCV . Another study suggested that HCV can be transmitted to the neonate as early as the first trimester, especially in women coinfected with HIV, which would potentially have implications on early organ development . Early transmission would potentially lead to long‐term tolerance to HCV antigens and loss of pathogen‐specific immune competence, although there are limited clinical data to support this.…”
Section: Hcv Infection In Childrenmentioning
confidence: 99%
“…(38) Another study suggested that HCV can be transmitted to the neonate as early as the first trimester, especially in women coinfected with HIV, which would potentially have implications on early organ development. (39) Early transmission would potentially lead to long-term tolerance to HCV antigens and loss of pathogen-specific immune competence, although there are limited clinical data to support this. (29) Abbreviations: C-section, cesarean section; CVS, chorionic villus sampling; ROM, rupture of membranes.…”
Section: Hcv Infection In Childrenmentioning
confidence: 99%